Goodness-of-Fit Tests for Inverse Ishita Distribution and Its Application on Renewable Energy Data in the Kingdom of Saudi Arabia (Global Journal of Sciences, 2025)
In this article, we presented the goodness-of-fit tests for the inverse Ishita  distribution with one parameter based on complete sample. Moreover, the  maximum likelihood estimation method was used to estimate the unknown  parameter of the distribution. In addition, a Monte Carlo simulation was also  performed to verify the behavior of the maximum likelihood estimator.  Ultimately, we applied the proposed distribution on renewable energy data in  Saudi Arabia and compared it with Weibull and Shanker distributions.
Keywords: Inverse Ishita distribution; Goodness-of-fit tests; Max likelihood; estimator Simulation.